1992
DOI: 10.1159/000110937
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Prostate Cancer: What Do Their Similar Geographies Suggest?

Abstract: Mortality rates from multiple sclerosis show a well-known north-south gradient, both within the United States and internationally. Mortality rates from prostate cancer show a similar gradient and are significantly correlated with multiple sclerosis (MS) mortality and MS prevalence. This finding adds prostate cancer to the set of diseases whose geographic distributions are significantly correlated with MS and whose members include colon cancer, dental caries, and Parkinson''s disease. Review of the literature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…However, the epidemiological evidence from our study is weak, because the excess in mortality from multiple sclerosis is based on small numbers, is concentrated in the low-exposure subcohort, and declines when state referent rates are used (the distribution of multiple sclerosis is related to geographic latitude [Schwartz, 1992]). Kolstad et al [1995] did find an increased mortality rate ratio for degenerative disorders of the nervous system (multiple sclerosis, Parkinsonism, and motor neuron disease) of 1.8 (CI 0.9-3.8) in a Danish styrene cohort.…”
Section: Discussionmentioning
confidence: 73%
“…However, the epidemiological evidence from our study is weak, because the excess in mortality from multiple sclerosis is based on small numbers, is concentrated in the low-exposure subcohort, and declines when state referent rates are used (the distribution of multiple sclerosis is related to geographic latitude [Schwartz, 1992]). Kolstad et al [1995] did find an increased mortality rate ratio for degenerative disorders of the nervous system (multiple sclerosis, Parkinsonism, and motor neuron disease) of 1.8 (CI 0.9-3.8) in a Danish styrene cohort.…”
Section: Discussionmentioning
confidence: 73%
“…A link between vitamin D and multiple sclerosis (MS) was suggested in 1974 [1] and again in 1992 [2]. However, the first proposed mechanism, weak myelin formation in vitamin D-deficient youth, lacked experimental support and was not entirely consistent with the natural history of MS, so the hypothesis languished.…”
Section: The Vitamin Demultiple Sclerosis Hypothesismentioning
confidence: 99%
“…Again, he proposed that lack of vitamin D may be a causative factor in both diseases. 114 Another study conducted to determine the association of sunlight exposure with prostate cancer risk showed that sun exposure and VDR polymorphisms together play an important role in the etiology of prostate cancer. Interview data on lifetime sun exposure and other risk factors were collected for 905 non-Hispanic white men (450 cases and 455 controls).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%